The Values of Multicultural Education According to Modern Tafsir: A Thematic Study of Tafsir al-Maraghi and Tafsir al-Mishbah - Salamudin, Ceceng; Abdullah, Deba Muslim; Maria, Anly (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2024)
Many horizontal conflicts and acts of violence arise from erroneous human perspectives on social, cultural, and religious diversity. In Islam, the Qur’an functions as a fundamental source of values and paradigms guiding Muslim attitudes toward such differences. This study examines the values of multicultural education derived from modern Qur’anic interpretations of QS. Al-Baqarah [2]: 62, 213, 256, an-Nisa [4]: 36, 135; al-Maidah [5]: 2, Ali-Imran [3]: 15, 134, al-Ḥujurāt [49]:11-13, a verse that explicitly addresses human diversity, equality, and moral merit based on piety (taqwā). The research focuses on Tafsir al-Maraghi and Tafsir al-Mishbah, selected as representative works of modern tafsir due to their rational, contextual, and socio-ethical approaches to Qur’anic interpretation. Using a descriptive qualitative method with a thematic (mawḍū‘ī) interpretation approach, the study analyzes how these tafsir conceptualize diversity and social relations. The findings indicate that articulate four core values of multicultural education: (1) learning to live with differences, (2) mutual respect among individuals and groups, (3) interdependence among human beings, and (4) non-violent conflict resolution and reconciliation. Rather than offering direct or complete solutions to conflict and violence, these values provide a conceptual and ethical framework that can contribute to the development of multicultural awareness and peaceful coexistence in plural societies.